Expatriation as a Sentence: An Existential Reading of “Del país de la pena” by Hanni Ossott (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
The purpose of this paper is to develop an existential reading of the poem “Del país de la pena” written by the Venezuelan poet Hanni Ossott with the aim of thinking the term “expatriation” as a philosophical concept. Following a historical introduction that seeks to situate Ossott’s poem within a poetic tradition that tries to recuperate the feeling of strangeness in the face of the properly national, this essay attempts to trace the interpretative and methodological horizons of the poem through a reading of the essay “Paysage avec dépaysement” [Uncanny Landscapes] written by the French philosopher Jean- Luc Nancy. The reading of Nancy’s essay will facilitate the existential reading of Ossott’s poem with which the present essay will seek to demonstrate the philosophical richness of this poem and the way in which it thematizes expatriation. By way of conclusion, it will be suggested that expatriation can be understood as a sentence, but not necessarily in a negative manner; rather, it can be thought through a positive valence that can aid in the contemporary conceptualization about Latin America.